Functional Reproductive and Developmental Traits Differences Between Two Macrocystis Ecomorphs: Importance of Neutral Lipids - Camilo Rodríguez‐Villegas; Alejandro H. Buschmann; Mayra A. Barrios; Sandra Pereda; Carolina Camus; Pamela Fernández; María C. Hérnandez‐González; Ángela M. Baldrich; Cynthia Urrutia; Ailen M. Poza; Karina Villegas; Camila Martínez; et al. (Ecology and Evolution, 2025)
ABSTRACT The kelp genus Macrocystis presents populations recognizable by distinct morphological traits, which has raised discussions on its taxonomical status. Recently, whole genome sequencing arose global evidence of Macrocystis ecomorphs “integrifolia” and “pyrifera” being genetically distinct. In the southern hemisphere, both ecomorphs maintain a separated distribution that coincides, without overlap, in the area of 33° S. Besides the fact that both ecomorphs are interfertile, at least under laboratory conditions, several differences in their reproductive strategies and early developmental traits have arisen in over 20 years of ecological and ecophysiological studies. In this study, we evaluated the content of neutral lipids in zoospores of both ecomorphs as a proxy of the required energy to swim and settle. The finding showed that zoospores of “integrifolia” ecomorph have a significantly lower level of neutral lipids than the southern “pyrifera” ecomorph. This correlates with the lower motility of the cells and lower germination capacity in the ‘integrifolia’ ecomorph, which has been consistently seen over the years. Further, we have seen a highly consistent pattern of a higher zoospore production, germination rate, sexual reproductive success, and early developmental performance (growth and survival) of juvenile sporophytes of “pyrifera” compared to “integrifolia.” Hence, both ecomorphs show, in addition to genetic and morphological differences, differential reproductive functional traits consistent in time and space that further support the hypothesis of an ongoing separation of these two Macrocystis ecomorphs.